Juhudun muqabalatun annaskhatun almakhtutotun ma'a annuskhatun almatbu'ah : Hululun inda adamun rijhanun ihdahuma tahkikun aljami'un alkabirun namuzajan / Siria Ahmad - Ahmad, Siria (Academy of Contemporary Islamic Studies, 2015)
The endeavours attained in treating Islamic manuscripts as proper as they deserve are obvious among academicians, for being predominantly well-preserved in related entities. Furthermore, the fraternity of Islamic philologists added another feather to their hat for holding steadfastly to editing the legacy of texts, one after another. Routinely, once each philologist intends to edit a scripture, he is required to be in access to all surviving versions of it. Out of the common, there is occurrence of dealing with a sole version. This paper will delve into the deep exemplified by an attempt achieved in editing 403 hadith of Musnad Ali ibn Abi Talib under the Division of Doings from the book al-Jami' al-Kabir by al-Sayuti. The fraction of the colossal masterpiece is a ground for the case mentioned which the author herself had edited it with assistance of improper transcript. In an attempt to raise the matter from blur to clear, this paper carries out an analytical study on the predicaments derived from flaws of both sides which undoubtedly require alternatives. This filling of gaps accentuates the importance of proficiency in terms of language, field and ropes of the manuscript combined with traits of patience, sincerity and well-observance.